Gestión ambiental de residuos sólidos domiciliarios en el distrito de Los Olivos - Alvarado Flores, Alexis Martín (Universidad Nacional Federico Villarreal, 2002)
Gestión ambiental de residuos sólidos domiciliarios en el distrito de Los Olivos
Keywords: Gestión; Ambiental; Residuos; Sólidos; Domiciliarios; Distrito; Olivos; https://purl.org/pe-repo/ocde/ford#2.07.01